Merchandising en la Comercializadora “MEGA PROPRINEC” - Campos Salvatierra, Lolifer Carolina (2020)
This research is based on the analysis of the application of Merchandising techniques in the marketing company MEGA PROPRINEC because an extensive problematic situation is observed due to an inadequate distribution of the products on the hangers, inappropriate management of stock management, lack of price labels, through the different perspectives of both customers and employees and that the owner still recognizes as the main weakness the inadequate infrastructure that causes difficulty in the circulation of customers and causes somewhat more difficulty in using the different strategies merchandising at the point of sale.